(untitled) (Archives of Mechanics - Test, 2007)
This article presents the results of experimental and numerical work on the dynamic electroelastic response of Rosen-type piezoelectric transformers. Experiments were conducted to measure the electrical impedance, phase angle and voltage gain at various frequencies. The three-dimensional finite element method was also employed to solve the coupled electro-elastic boundary value problem. The electrical impedance, phase angle and voltage gain were calculated and a comparison was made between experiment and simulation. The effects of load resistance and capacitance on the voltage gain and electroelastic field concentrations were also discussed in detail.